Efektivitas Penggunaan Kitab Silsilatu Ta’lim Al Lughoh Al ‘Arabiyyah pada Mata Pembelajaran Shorof Terhadap Kemampuan Merubah Dhomair Af’al Kelas VIIID MTs Pondok Pesantren Darul Hijroh Polokarto - Nur Dinna Islamiatun (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2023)
The Selection and Determination of Textbooks as Student Learning Materials Is a Very Urgent Matter. It is essential to select a good and appropriate textbook to improve students’ comprehension quality. This research was conducted to examine the process of shorof (morphology) learning using the book Silsilatu Ta’lim Al-Lughoh Al-‘Arabiyyah, to assess the effectiveness of using Silsilatu Ta’lim Al-Lughoh Al-‘Arabiyyah in the shorof subject on students’ ability to transform verb pronouns (dhomair af‘al), and to identify the strengths and weaknesses of using the book Silsilatu Ta’lim Al-Lughoh Al-‘Arabiyyah. This research is a field study using a quantitative approach. The total population was 26 female students. Data collection techniques included questionnaires, tests, interviews, observations, and document analysis. Based on the obtained data, it can be concluded that shorof learning using Silsilatu Ta’lim Al-Lughoh Al-‘Arabiyyah is considered effective. The final questionnaire data showed a result of 65.38%, which falls into the “effective” category. Meanwhile, the test results on the ability to transform verb pronouns (dhomair af‘al) showed an average score of 88.85. In the shorof learning process, the teacher used the lecture method, supplemented with other methods, allowing the learning process to run effectively and efficiently. The strengths of using Silsilatu Ta’lim Al-Lughoh Al-‘Arabiyyah include: a wealth of supporting material, easily understandable language, and summary sections at the end of each chapter. The weaknesses include: an unappealing design, presentation of themes that are less relevant to current developments, and illustrations/images that are less engaging.